2004
DOI: 10.1002/ange.200352931
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Hyperconjugation in Ethane: A Perspective from Ab Initio Valence Bond Theory

Abstract: Abgedreht: Ab‐initio‐VB‐ und ‐BLW‐Methoden werden zur Abschätzung der Beiträge von Hyperkonjugation sowie von sterischen Effekten zur Rotationsbarriere in Ethan verwendet. Die Ergebnisse belegen, dass Hyperkonjugation das gestaffelte Konformer mit etwa 4 kJ mol−1 gegenüber der ekliptischen Form stabilisiert (siehe Bild). Sterische Hinderung ist allerdings das wichtigste Kriterium für die Bevorzugung der gestaffelten Konformation in Ethan. BLW=Block‐localized wavefunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…All these effects are hyperconjugative interactions [34] of the target bonds with the wing bonds, and as such are much smaller than the D in-situ values due to the direct CÀC bonding. Thus, even though it is interesting to note that the higher propellanes have significant hyperconjugative interactions, of the inverted bond with the wing bonds, these energetic effects do not affect the conclusions in this paper, and are hence tabulated in the SI (Table S.6).…”
mentioning
confidence: 90%
“…All these effects are hyperconjugative interactions [34] of the target bonds with the wing bonds, and as such are much smaller than the D in-situ values due to the direct CÀC bonding. Thus, even though it is interesting to note that the higher propellanes have significant hyperconjugative interactions, of the inverted bond with the wing bonds, these energetic effects do not affect the conclusions in this paper, and are hence tabulated in the SI (Table S.6).…”
mentioning
confidence: 90%
“…Pauli repulsion; Pauli repulsion = exchange ? repulsion; almost all of them contradict Bader et al's SCF assignment of less steric repulsion in S versus E. Valence bond analyses concluded that while S is favored by way of hyperconjugation, ''steric'' repulsion in E is responsible for 66 % [28] or more [29] of the barrier height. Su and Li [30], on the basis of a union of methyl radicals, assigned a cumulative D(exchange ?…”
Section: Ethane's Rotational Barriermentioning
confidence: 87%
“…The geometry optimizations with these deletions were obtained at 6-31G(d) and 6-311G(3df,3pd) basis sets with Hartree−Fock method. 8,10 The potential energy surface (PES) scanning, varying R C2−H7 /θ and R C1−C2 /θ for the ionic ethanol (the angle θ made by the O−H bond with C−C− O plane, Figure 1), were calculated at the B3LYP/6-31G* level. The accurate dissociated energies of the two conformers were calculated with the M06-2X (at the 6-311++G(d,p) and 6-311+ +G(3d,p) basis sets) and MP2/aug-cc-pvdz methods.…”
Section: Methodsmentioning
confidence: 99%